Effects on asthma and respiratory allergy of Climate change and air pollution. Issue 1 (December 2015) - D'Amato, Gennaro; Vitale, Carolina; De Martino, Annamaria; Viegi, Giovanni; Lanza, Maurizia; Molino, Antonio; Sanduzzi, Alessandro; Vatrella, Alessandro; Annesi-Maesano, Isabella; D'Amato, Maria
Abstract The major changes to our world are those involving the atmosphere and the climate, including global warming induced by anthropogenic factors, with impact on the biosphere and human environment. Studies on the effects of climate changes on respiratory allergy are still lacking and current knowledge is provided by epidemiological and experimental studies on the relationship between allergic respiratory diseases, asthma and environmental factors, like meteorological variables, airborne allergens and air pollution. Epidemiologic studies have demonstrated that urbanization, high levels of vehicle emissions and westernized lifestyle are correlated with an increased frequency of respiratory allergy, mainly in people who live in urban areas in comparison with people living in rural areas. However, it is not easy to evaluate the impact of climate changes and air pollution on the prevalence of asthma in general and on the timing of asthma exacerbations, although the global rise in asthma prevalence and severity could be also considered an effect of air pollution and climate changes. Since airborne allergens and air pollutants are frequently increased contemporaneously in the atmosphere, enhanced IgE-mediated response to aeroallergens and enhanced airway inflammation could account for the increasing frequency of respiratory allergy and asthma in atopic subjects in the last five decades. Pollen allergy is frequently used to study the interrelationship between air pollution and respiratory allergic diseases such as rhinitis and bronchial asthma. Climatic factors (temperature, wind speed, humidity, thunderstorms, etc) can affect both components (biological and chemical) of this interaction. Scientific societies should be involved in advocacy activities, such as those realized by the Global Alliance against chronic Respiratory Diseases (GARD).